(untitled) (Journal of Enam Medical College, 2020)
Background: Use of Duplex Color Doppler Sonography is gaining increasing popularity for assessment of blood vessels in various disease processes around the world. The past 20 years have seen an enormous growth in both technical aspects of Doppler ultrasound and its application in obstetric and fetal medicine. Objective: This cross-sectional study was carried out to observe Doppler wave form in subjects with preeclampsia. Specific objective was to see RI and PI in different groups of study subjects from 24th to 37th weeks and find out significant difference of different Doppler indices between two groups (i.e., to calculate the proportion of subjects having early diastolic notch in two groups). Materials and Methods: Enrolling 40 subjects with preeclampsia, this study was done in the Department of Radiology & Imaging, Dhaka Medical College Hospital, Dhaka, over a period of six months from 20th June 2014 to 19th December 2014. A total number of 40 normal pregnancies were also included for comparison. Results: Majority (35% in normal and 37.5% in preeclampsia) of the respondents were found in the age group of 21−30 years. Unpaired t-test revealed no significant difference between mean age of two groups. Among normal group, mean±SD of PI and RI were 1.12±0.0846 and 0.571±0.058 respectively and in preeclamptic group mean PI and RI were 2.497±0.369 and 0.8255±0.087. There was statistically significant (by unpaired t-test) difference in mean Doppler indices between these two groups. Early diastolic notch was found in 90% subjects with preeclampsia and 5% subjects with normal pregnancy. Chi-square test showed that there was statistically significant difference regarding presence of early diastolic notch between normal regarding subjects and subjects with preeclampsia. Conclusion: From the study result it was concluded that Doppler indices with presence of early diastolic notch are reliable indicators for early detection of preeclampsia. J Enam Med Col 2020; 10(1): 33-38